Merger of Public Sector Banks : A Case of Chennai Bank Ltd. and Bhopal Bank Ltd. - Yadav, Rajesh Kumar; Mohania, Sarvesh (Prabandhan: Indian Journal of Management, 2020)
Chennai Bank Ltd. is the leading South Indian commercial bank having more than 2,875 small and large size branches all across the Southern states of India. It was established in the year 1966 just after the nationalization of private banks in India. Bhopal Bank Ltd. is one of the oldest banks of India founded by the Nawabs of Bhopal. After nationalization, it started working under the umbrella of the Government of India. Over a decade, increase in the number of non-performing assets, declining contribution of selected public sector banks, and expanding private sector role as banks or non-banking financial companies, etc. are few points of observation, which led to a new idea of merging up of public sector banks. This case study discussed why the Government of India has strategically decided to merge Chennai Bank Ltd. and Bhopal Bank Ltd. and what changes and challenges this merger will bring such as post-merger restructuring, struggle for financial stability, difference in organizational culture, employee layoffs, difference in demographic customer database, and opening up or shutting down of branches due to increase in numbers of branches, etc.